Antioxidant activity of exopolysaccharides from marine cyanobacteria - Pinaki Hazra; Sahana Ghosh; Puspita Roy; Debopam Sinha; Gargi Saha Kesh (The Microbe, 2025)
With increasing evidence, it is suggested that oxidative damage to cell machinery by unessential formation of oxygen free radicals in excess has a significant role in many human diseases. Natural products with antioxidant properties have capability to reduce their generation or at the minimum stop their advancement and metastasis in the organism. Extracellular polysaccharides (EPS) from cyanobacteria possess commercially noteworthy physiological and therapeutic properties. This significant group of biomolecules demonstrate ability to eliminate reactive oxygen species (ROS) that are formed inside our body by a variety of metabolic reactions.The current study deals with the in vitro antioxidant potential of EPS isolated from two halophilic marine cyanobacteria from Sundarbans, namely Oxynema aestuarii AP24 and Euryhalinema mangrovii AP9F. A maximum concentrations of 0.1405 gm /100 ml and 0.1072 gm /100 ml of EPS were obtained from AP24 and AP9F, respectively. Total carbohydrate and protein were estimated from the crude EPS. The water holding capacity of the EPS from AP 24 & AP9F were 189 % and 217 %, respectively. Oil holding capacity of EPS from AP24 was 103 % and AP 9 F was 204.5 %. 50 mg/ml of EPS from AP24 and AP9F showed 76 % and 64 % flocculating activity respectively. In a comparable assay, ascorbic acid as standard reference compound has IC50 (DPPH scavenging activity) value of 391.85 µg/ml and IC50 value of EPS from AP24 is 564±1.393μg/ml & IC50 value of EPS from AP9F is 769.01±1.759 μg/ml. IC50 (Hydrogen Peroxide scavenging activity) values for EPS from AP24 and AP9F were 857.6±1.035 µg/ml and 1003±1.126 µg/ml where as for ascorbic acid it was 492.99±1.117 µg/ml. Reducing power of EPS from AP24 & AP9F showed a comparable value with respect to ascorbic acid standard and demonstrated increase with increasing concentration. Certain spectral features from FTIR spectroscopy collectively confirm the formation of exopolysaccharides in the cyanobacterial extract.Different methods have been used to elucidate the antioxidant capacity of the exopolysaccharides extracted from AP24 & AP9F. In this paper, the detailed study of the EPS from both the strain will add significant value in the research field of bioactive compounds of cyanobacteria in the future.